Sno2-reduced graphene oxide nanocomposite for ethanol sensing at room temperature - Zito, C. A. [UNESP]; Volanti, D. P. [UNESP] (Wiley, 2017)
Nanocomposites based on metal oxide semiconductors and reduced graphene oxide (RGO) have been proposed as gas sensors to respond at room temperature. In this work, we prepared SnO2-RGO nanocomposite by microwave-assisted hydrothermal (MAH) method in one-step. The combined characterization techniques including X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, field emission-scanning electron microscopy (FESEM), energy dispersive spectroscopy (EDS) and transmission electron microscopy (TEM) confirm the formation of SnO2-RGO nanocomposite, and the distribution of SnO2 nanoparticles on RGO surface. The gas sensing performance of SnO2-RGO was evaluated by ethanol exposure at room temperature (21 °C). The results of gas sensing performance reveal that SnO2-RGO sensor has a great response to ethanol at room temperature, with a response time of about 100 seconds for the highest concentration of the gas (1,500 ppm). Moreover, it was found that the sensor has a higher selectivity for ethanol than for methanol. It is considered that RGO plays an important role in the gas sensing response.